A novel surgical technique: Crushed septal cartilage graft application in endonasal septoplasty. Issue 2 (April 2019) - Mutlu, Vahit
Abstract: Objective: Nowadays, different septoplasty procedures are applied for therapy of nasal septum deviation. However, various complications of the septoplasty procedures have been described. Several techniques have been developed to decrease the incidence of these complications by surgeons. We aimed to present the effectiveness of the crushed septal cartilage graft, which is a novel septoplasty technique. Methods: Patients: Patients The study was performed based on the parameters of 500 patients who underwent surgery with crushed cartilage graft technique in our clinic between the dates 2013 and 2016. Technique: This novel operation technique was performed under general anestesia. The NOSE (Nasal obstruction symptom evaluation) scale was applied to all patients in both the preoperative period and the 2nd month of the postoperative period, and then the both values were statistically compared. Additionally, all the patients were followed up for complications that may occur after the operation for a year. Results: The study included 140 (28%) female and 360 (72%) male patients, which totally makes 500 patients. The average age of the participants was 35 ± 12.5. When compared to the preoperative NOSE scale values (P ˂ 0.001), the postoperative NOSE scale values were found to be significant. We watched intranasal infection and incrustation in 7(1.4%) patients in early postoperative period and the epistaxis in 3(0.6%) patients in late postoperative period. We did not see any postoperative complications apart from these two minor and insignificant complications during the follow-up along a year. Conclusion: The crushed cartilage technique is a feasible, safe and effective alternative surgery technique to traditional septoplasty. What is more, complications of septoplasty can be prevented with the help of this novel surgical technique.